Development Of Canva-Based Interactive E-books in Consumer Education Courses in Culinary Arts Study Programs - Vina Gabriella Saragih; Aditiya Pratama Daryana; Prima Yudisthira; Amalia Akita (International Journal of Educational Development and Innovation, 2026)
This study aimed to develop a Canva-based interactive e-book for the Consumer Education course in the Culinary Arts Study Program and to examine its feasibility, practicality, and effectiveness in improving students’ learning outcomes. The research used a Research and Development (R&D) approach with the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants in this study were students of the Culinary Arts Study Program who took the Consumer Education course. Data were collected through validation questionnaires completed by material experts, media experts, and language experts, student response questionnaires, and learning achievement tests in the form of pre-tests and post-tests. The findings showed that the Canva-based interactive e-book had a very high level of feasibility, with scores of 100% from the material expert, 88.24% from the media expert, and 95% from the language expert, all of which were categorized as highly feasible. In terms of practicality, the small-scale trial reached 82.8%, while the large-scale trial reached 89.16%, indicating that the e-book was highly practical for classroom use. The results also revealed a significant improvement in students’ learning outcomes, with the average score increasing from 80.30 in the pre-test to 95.20 in the post-test, and all students achieving mastery learning after the implementation. In conclusion, the developed Canva-based interactive e-book is feasible, practical, and effective as a learning medium for the Consumer Education course in the Culinary Arts Study Program. It also helps improve students’ understanding, engagement, and independent learning.